PENERAPAN ANALASIS COST VOLUME PROFIT DALAM PERENCANAAN LABA (STUDI KASUS PADA UD REJO MULYO SURABAYA) - JELITA SAKTI, VINCENSIA Jelita (Jurnal Akuntansi AKUNESA, 2013)
Cost Volume Profit is a device which functioned on decision planning and taking. Analysis ofCost Volume Profit (CVP) emphasizes the relationship among cost, sold volume, and price, soall financial information will be included. That research is a case study analysis that is appliedon a company namely UD Rejo Mulyo Surabaya, because the company has not done the analysiscost volume profit. Therefore, the aim of this research is trying to give financial informationabout cost analysis, volume, and profit. This research used is descriptive-qualitative method withquantitative data. Several elements which are useful in cost volume analysis profit analysis are:Contribution Margin Analysis, Break Even Point Analysis, Margin of Safety Analysis, andOperating Leverage Analysis. Based on the analysis, we concluded that plastic production tendto has a big profit contribution to the firm. Keyword: Cost Volume Profit, Contribution Margin Analysis, Break Even Point Analysis,Margin of Safety Analysis, Operating Leverage Analysis.